2021
DOI: 10.1186/s43055-021-00586-y
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced mammography in comparison with dynamic contrast-enhanced MRI: which modality is appropriate for whom?

Abstract: Background Dynamic contrast-enhanced MRI (DCE-MRI) is a revolution regarding screening and diagnosis of breast cancer. Yet, sometimes it is not the appropriate choice of imaging since the examination needs to be scheduled and may take place in another department. Contrast-enhanced mammography (CEM) is contrast-based digital mammogram, and consequently, it has emerged as a potential and promising replacer to DCE-MRI. Main body of the abstract There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
(55 reference statements)
0
8
0
9
Order By: Relevance
“…Contrast-enhanced mammography (CEM) is almost as sensitive as MRI and is much less expensive but has been far less evaluated for screening and is not yet Health Canada approved for screening. [44][45][46] CEM in addition to mammography can increase sensitivity from 71.5% to 92.7% and specificity from 51.8% to 67.9%. 47 Another study showed 13 of 14 cancers (93%) occult on mammography but seen on CEM were in women with dense breasts.…”
Section: Jurisdiction (Province or Territory)mentioning
confidence: 99%
“…Contrast-enhanced mammography (CEM) is almost as sensitive as MRI and is much less expensive but has been far less evaluated for screening and is not yet Health Canada approved for screening. [44][45][46] CEM in addition to mammography can increase sensitivity from 71.5% to 92.7% and specificity from 51.8% to 67.9%. 47 Another study showed 13 of 14 cancers (93%) occult on mammography but seen on CEM were in women with dense breasts.…”
Section: Jurisdiction (Province or Territory)mentioning
confidence: 99%
“…3D mammography (or called tomosynthesis) produces X-ray images of the breast by taking various views across the breast in an arc. Previous studies reported that the detection is significantly improved when 3D mammography was used with 2D mammography [42]. A mammography expert, often known as a mammographer, performs this process.…”
Section: Mammographymentioning
confidence: 99%
“…El avance en los métodos imagenológicos en los últimos años ha hecho que la elección del más adecuado para la realización de un diagnóstico resulte un desafío 1 .…”
Section: Introductionunclassified
“…En la actualidad hay falta de consenso acerca de sus indicaciones, pudiendo ser similares a las de la resonancia magnética (RM) de mama. Entre ellas se mencionan algunas como detección de cáncer de mama, estadificación preoperatoria, caracterización de hallazgos indeterminados y seguimiento de la respuesta a la terapia neoadyuvante 1,[4][5][6] .…”
Section: Introductionunclassified